Predictors of Acute and Chronic Undernutrition among 10-19 Years Adolescents using World Health Organisation Growth References: A Cross Sectional Study from Central India - Bali, Surya; Gouroumourty, Revadi (Nepal Journal of Epidemiology, 2024)
Background: Adolescence, a period of rapid growth and development with biological and physiological changes, is influenced by socioeconomic, cultural, and behavioural factors. There is a dearth of data regarding undernutrition in 10-19 year olds in India. The study’s objective was to estimate the prevalence of thinness and stunting in adolescents using World Health Organization (WHO) references and its determinants. Methods: This cross-sectional study represents the baseline of an adolescent health survey (November 2017 to March 2018) of 3,213 adolescents. Participants were selected using a multi-stage stratified random sampling technique from six districts of Madhya Pradesh. Data were collected by field investigators through a paperless real-time method and analyzed using R and the WHO anthro plus analyzer. Results: The prevalence of thinness and stunting were 17.1% and 23.3% respectively. Thinness was profound in early adolescents and stunting in late adolescents. While adolescent boys showed a higher prevalence of thinness, girls showed a higher stunting burden. Negative binomial mixed model regression revealed that early adolescents and boys were more likely to develop thinness. Similarly, the likelihood of stunting was higher among late adolescents, girls, and adolescents belonging to categories other than general. Fathers’ education was protective against stunting irrespective of whether they were above or below primary education. Conclusion: Screening of all adolescents may be undertaken using WHO references in the national surveys for planning interventions targeted to malnourished adolescents to prevent micronutrient deficiencies and intergenerational consequences.